Pendampingan Implementasi Project Based Learning di SMK - Susilaningsih, Susilaningsih; Siswandari, Siswandari; Muchsini, Binti; Jaryanto, Jaryanto; Hamidi, Nurhasan (Universitas Negeri Makassar, 2024)
As an effort to restore the quality of learning during the pandemic, the Government issued the Merdeka Curriculum. One of the main characteristics of the independent curriculum is Project Based Learning (PjBL) for the development of soft skills and character according to the Pancasila student profile. Because this independent curriculum is still new, many teachers are not ready to implement PjBL properly. This Community Service activity aims to improve the readiness of teachers, members of the Accounting MGMP in the city of Surakarta, in implementing Project Based Learning (PjBL) in Vocational High Schools (SMK). The implementation of activities uses the Training and Assistance method whose planning is based on existing problems and during the process reflection and evaluation are carried out. This activity can increase teacher awareness of the importance of PjBL in the implementation of the Independent Curriculum; increase teacher understanding in planning PjBL; motivating teachers to implement PjBL in their teaching, so that the students having Pancasila Student Profile and Work Culture. The recommendation given is that training and mentoring should be carried out on an ongoing basis, teachers are given examples of good practices for implementing PjBL, so that it can make it easier for teachers to plan and implement PjBL properly.